Landasan Filosofis Pendidikan Sebagai Dasar Penanaman Karakter - Ulinuha, Widda; Fadillah, Ilah; Hidayat, Soleh (LPPM Institut Pendidikan Nusantara Global, 2024)
The aim of this research is to find out how the philosophical foundations of education view student character education. As an educational institution, schools are not only tasked with educating students and creating a good learning environment, but are also expected to develop good character in students. If in relation to learning, national education must be accessible to students, then schools must also be able to shape students' characters better. We know that students are great imitators of adults, positive attitudes, let alone negative attitudes, are easy for students to imitate. Therefore, teachers must always show good character to their students, and the nation's prospective students are expected to have good character in addition to cognitive intelligence. The research method uses a library research approach, where previous research is summarized from library sources, documents and scientific journals. The information collected is analyzed to achieve in-depth understanding through library research by processing and collecting various types of secondary data from the surrounding environment. This philosophical foundation becomes a guideline that guides the creation of a comprehensive character education program, including ontological, epistemological and axiological aspects. The philosophical foundation thus not only provides a conceptual basis, but also a practical basis that guides the implementation of character education.